Skewed maturation of memory HIV-specific CD8 T lymphocytes. - Champagne, P; Ogg, G; King, A; Knabenhans, C; Ellefsen, K; Nobile, M; Appay, V; Rizzardi, G; Fleury, S; Lipp, M; Förster, R; Rowland-Jones, S; et al. (2001)
Understanding the lineage differentiation of memory T cells is a central question in immunology. We investigated this issue by analysing the expression of the chemokine receptor CCR7, which defines distinct subsets of naive and memory T lymphocytes with different homing and effector capacities and antiviral immune responses to HIV and cytomegalovirus. Ex vivo analysis of the expression of CD45RA and CCR7 antigens, together with in vitro analysis of the cell-division capacity of different memory CD8+ T-cell populations, identified four subsets of HIV- and CMV-specific CD8+ T lymphocytes, and indicated the following lineage differentiation pattern: CD45RA+ CCR7+ --> CD45RA- CCR7+ --> CD45RA- CCR7- --> CD45RA+ CCR7-. Here we demonstrate through analysis of cell division (predominantly restricted to the CCR7+ CD8+ T-cell subsets) that the differentiation of antigen-specific CD8+ T cells is a two-step process characterized initially by a phase of proliferation largely restricted to the CCR7+ CD8+ cell subsets, followed by a phase of functional maturation encompassing the CCR7- CD8+ cell subsets. The distribution of these populations in HIV- and CMV-specific CD8+ T cells showed that the HIV-specific cell pool was predominantly (70%) composed of pre-terminally differentiated CD45RA- CCR7- cells, whereas the CMV-specific cell pool consisted mainly (50%) of the terminally differentiated CD45RA+ CCR7- cells. These results demonstrate a skewed maturation of HIV-specific memory CD8+ T cells during HIV infection.